Asia-Pacific contemporary finance and development - Barnett, William A.; Sergi, Bruno S. (International symposia in economic theory and econometrics, 2019)
This volume of The International Symposia in Economic Theory and Econometricsexplores and investigates contemporary challenges and issues facing the Asia-Pacific economies. For researchers and students of economics and finance, this volume is a fascinating exploration of emerging topics in one the fastest growing economies in the world.